The new elementary teacher's handbook flourishing in your first year - Jonson, Kathleen Feeney; Cappelloni, Nancy; Niesyn, Mary.; Sage eBooks (Thousand Oaks, Calif. : Corwin, 2011)
This comprehensive guide from veteran educators gives first-year teachers a multitude of classroom-tested strategies for those critical first days of school. The authors walks you through setting up your classroom, managing behaviour, planning lessons assessing students' performance and partnering with families.
Specialized.
Description based on print version record.
Includes bibliographical references.
Keywords: First year teachers -- United States -- Handbooks, manuals, etc; Elementary school teachers -- United States -- Handbooks, manuals, etc; Elementary school teaching -- United States -- Handbooks, manuals, etc; Electronic books